Effect of Dietary Supplementation of Bioactive Peptides on Antioxidant Potential of Broiler Breast Meat and Physicochemical Characteristics of Nuggets - Aslam, Sadia (Food Sci Anim Resour, 2020)
Poultry meat is generally exposed to quality deterioration due to lipid oxidation during storage. Oxidative stability of meat can be increased by feed supplementation. Aim of the current study was to investigate the effect of dietary supplementation of fish waste derived bioactive peptides on antioxidant potential of broiler breast meat and physico-chemical characteristics and quality parameters of nuggets prepared from breast meat. 180 broiler birds (six groups of 30 birds) were purchased. Each group was given different concentrations of bioactive peptides i.e. 0, 50, 100, 150, 200, and 250 mg/kg feed. After completion of six weeks birds were slaughtered and breast meat was stored at −18°C for six months. Nuggets were prepared and stored at −18°C for 45 days. Meat samples were analyzed for antioxidant activity [total phenolic contents (TPC), DPPH(•) scavenging activity, and ferric reducing antioxidant power] and lipid oxidation assay at regular intervals of 1, 2, 3, 4, 5, and 6 months while nuggets were analyzed for quality (pH, color, texture and water holding capacity) parameters after regular interval of 15 days. A significant (p<0.05) effect of feed supplementation was observed on antioxidant status such as TPC, DPPH(•) scavenging activity, and FRAP of broiler breast meat. Dietary interventions of bioactive peptides significantly (p<0.05) delayed lipid oxidation of breast meat than control. All the quality parameters were also significantly affected due to dietary bioactive peptides and storage duration. Thus, dietary interventions of bioactive peptides can increase the antioxidant and shelf stability of broiler breast meat and nuggets.